FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT LULUSAN PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN JURUSAN TEKNIK SIPIL FT-UNP TERHADAP PROFESI GURU - Nurianda WFE Aromatika; An Arizal; Totoh Andayono (Universitas Negeri Padang, 2018)
Abstract— The background of this research related to the number of graduates from Technical Building Education Program; Department of Civil Engineering, Faculty of Engineering State University of Padang who choose to work on the field project rather than become a teacher. Therefore the purpose of this study is to reveal the factors that affect the interest of graduates from Technical Building Education Program; Department of Civil Engineering, Faculty of Engineering State University of Padang to the profession of teachers. The type of this research is descriptive quantitative with Proportional Random Sampling as sampling technique. The research data is obtained by spreading questionnaires to 78 graduates of Technical Building Education Program that has graduated from the Department of Civil Engineering in 2016. The results of the research showed that the external factors that affect the interest of graduates of Building Engineering Education Program to the profession the teacher is 78.81% or included in the high category. Therefore the highest value related to the sub indicators of society and campus.. Keywords: Interests, Vacancies and Professions